Transdisciplinary Learning: From Transversal Skills to Sustainable Development - Lavrinoviča, Beata (Acta Paedagogica Vilnensia, 2021)
The concept of transdisciplinarity has been extensively researched since the 1970s and still does not have one comprehensive definition, as it is considered highly context-dependent. Merging the knowledge synthesized by the scholars of transdisciplinary research, practice, and learning, transdisciplinary learning features have been identified and briefly elaborated on in this article, pointing out the functional and instructional nature of transdisciplinarity in modern education systems. Simultaneously, the article reflects on the connection of transdisciplinarity with the Education for Sustainable Development and transversal skills design, stating the significance of transdisciplinarity in tackling complex and uncertain social and environmental problems. As an approach, it promotes mutual and transformational learning, transcendence, problem-solving and transgression and is reflected in the values of active participation of learners and their orientation towards real-world problem-solving, blending disciplinary knowledge and constructing new knowledge, skills, competencies, and values collaboratively with peers, teachers, and the wider society.
Keywords: transdisciplinary learning; transversal skills; transformational learning; education for sustainable development